POOR FUNDING OF RESEARCH AND DEVELOPMENT: AN ACHILLES HEEL TO TECHNOLOGICAL GROWTH IN NIGERIA - OBIANAGWA, CHRISTOPHER EWUZIE; IFEM, LOUIEMARIE ADAEZE; UDEANI, NWAMAKA; UGWUOZOR, SAMUEL IFEANYI; NTE, EREFOROKUMA OROM; EZE , NKIRU UCHEDILICHUKWU (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2024)
The capacity of any society to produce its material needs is determined by the extent of development and transformation of its productive forces. Among the triad of productive forces, namely, the object of nature, labor power and instrument of labor, the last two- human ingenuity and technology stand out in the procurement of societal needs from the gifts of nature. Investment in research and development (R&D) offers the most reliable pathway through which progressive societies harness their human and material resources to create relevant technologies and effectively exploit the prodigality of nature for sustainable development. Meanwhile, the nexus between poor R&D funding and slow technological growth in Nigeria is understudied in the existing literature. The objective of the study was to ascertain if poor R&D funding is implicated in the slow growth of indigenous technology in Nigeria. Methodologically, the study relied on the qualitative data collected through secondary sources such as textbooks, journal articles, official documents, media reports, etc.; and analyzed them using qualitative descriptive method. The study revealed, among others, that meager budgetary allocation to education and R&D is implicated in the slow technological growth in Nigeria. Thus, the study recommended, inter alia, increased funding of R&D through broad-based public-private partnership